CASE STUDY OF POSITIVE CONFIRMED MALARIA IN SOUTHEAST SULAWESI BASED ON EPIDEMIOLOGICAL VARIABLES - Irma Irma; Yusuf Sabilu (Jurnal Farmasi Sains dan Praktis, 2021)
Malaria is one of the most common mosquito-borne infectious diseases in the world. Globally, deaths due to malaria infection reported in 2019 amounted to 405,000 deaths with a total number of sufferers of around 228 million cases. Although malaria cases have continued to decline in the last five years, including in Southeast Sulawesi Province, there are still regencies/cities in Southeast Sulawesi that have not been free from malaria. Therefore, this disease continues to be a burden of pain. This study aims to describe malaria cases in Southeast Sulawesi during the period from 2016 to 2020 based on epidemiological variables, namely people, place and time. The results showed that in general malaria cases from 2016 to 2020 showed a significant decline, based on place it can be seen that the Muna district was the area with the highest prevalence of malaria throughout the year of observation and North Konawe District as the area with the lowest malaria prevalence. From the people variable, the majority (67%) of malaria cases were men and only 33% were women. Meanwhile, based on the time in five years of observation, the highest malaria prevalence occurred in 2016 and the lowest was in 2020. Malaria prevention and control programs need to be carried out strictly to support the achievement of malaria elimination in all districts and cities in Southeast Sulawesi.